Comparative Study of Fucoidan from Saccharina japonica and Its Depolymerized Fragment on Adriamycin-Induced Nephrotic Syndrome in Rats - Jiaojiao Tan; Jing Wang; Lihua Geng; Yang Yue; Ning Wu; Quanbin Zhang (Marine Drugs, 2020)
Nephrotic syndrome (NS) is a clinical syndrome with a variety of causes, mainly characterized by heavy proteinuria, hypoalbuminemia, and edema. At present, identification of effective and less toxic therapeutic interventions for nephrotic syndrome remains to be an important issue. In this study, we isolated fucoidan from Saccharina japonica and prepared its depolymerized fragment by oxidant degradation. Fucoidan and its depolymerized fragment had similar chemical constituents. Their average molecular weights were 136 and 9.5 kDa respectively. The effect of fucoidan and its depolymerized fragment on adriamycin-induced nephrotic syndrome were investigated in a rat model. The results showed that adriamycin-treated rats had heavy proteinuria and increased blood urea nitrogen (BUN), serum creatinine (SCr), total cholesterol (TC), and total triglyceride (TG) levels. Oral administration of fucoidan or low-molecular-weight fucoidan for 30 days could significantly inhibit proteinuria and decrease the elevated BUN, SCr, TG, and TC level in a dose-dependent manner. At the same dose (100 mg/kg), low-molecular-weight fucoidan had higher renoprotective activity than fucoidan. Their protective effect on nephrotic syndrome was partly related to their antioxidant activity. The results suggested that both fucoidan and its depolymerized fragment had excellent protective effect on adriamycin-induced nephrotic syndrome, and might have potential for the treatment of nephrotic syndrome.